Digital Compensation for the Non Linearity of RF Amplifiers In Wideband Wireless Applications - Pasricha, Ruchi (My University, 2013)
The power amplifier’s nonlinearity broadens the input signal’s bandwidth. This is known as spectral re-growth which is undesirable since it causes interference with adjacent channels. The nonlinearity generates spectral re-growth, which leads to adjacent channel interference and violations of the out-of-band emission requirements mandated by regulatory bodies. It also causes in-band distortion, which degrades the bit error rate (BER) performance. To reduce the nonlinearity, the power amplifier can be operated at a lower power (“backed off”) so that it operates within the linear portion of its operating curve. Linearization techniques for nonlinear microwave power amplifiers have gained significant interest with the advent of spectrally efficient wireless communication systems. Most recent transmission schemes, such as Wideband Code Division Multiple Access (WCDMA) or Orthogonal Frequency Division Multiplexing (OFDM), are especially vulnerable to the nonlinear distortions due to high fluctuations in their power levels. To ensure that linearity is maintained to a high degree, it is necessary to examine the nature of amplifier distortion. Audio amplifier distortion is of concern for many years.
PHD, ECED
Keywords: BER; WCDMA; OFDM; ADPD